Aberrant c-AMP signalling in richter syndrome revealed by single-cell transcriptome and 3D chromatin analysis - Heng Li; Cheng Xing; Ji Li; Yihao Zhan; Ming Luo; Peilong Wang; Yue Sheng; Hongling Peng (Biomarker Research)
Abstract Richter syndrome (RS), characterized by aggressive lymphoma arising from chronic lymphocytic leukaemia (CLL), presents a poor response to treatment and grim prognosis. To elucidate RS mechanisms, paired samples from a patient with DLBCL-RS were subjected to single-cell RNA sequencing (scRNA-seq) and high-throughput chromosome conformation capture (Hi-C) sequencing. Over 10,000 cells were profiled via scRNA-seq, revealing the comprehensive B cell transformation in RS. Hi-C sequencing exposed a unique chromatin architecture in RS, with increased proximal and decreased distal interactions. At the compartment scale, the interaction between B compartments was strengthened in DLBCL cells, while topologically associating domains (TADs) in DLBCL had elevated intra-TAD and reduced inter-TAD contacts. Differentially expressed genes at TAD borders between CLL and DLBCL cells highlighted an enrichment of cAMP-mediated signalling. To substantiate the functional relevance of ATF1 and CAP1, the genes involve in cAMP-mediated signalling, in the context of cell proliferation, we have performed gain- and loss-of-function experiments in relevant cell lines. Collectively, integrated scRNA-seq and Hi-C data suggest that chromatin reorganization and altered cAMP signalling drive RS transformation.